An Overview Of The Knowledge Of People With Diabetes Mellitus About Diabetic Retinopathy: A Literature Review - Siswoyo; Widayati, Nur; Habibah, Nailatul (Journal of Rural Community Nursing Practice, 2023)
One of the complications of diabetes mellitus is diabetic retinopathy. The results of the research conducted to determine awareness and knowledge about diabetic retinopathy showed that awareness and knowledge about diabetic retinopathy were not satisfactory. Knowledge and awareness about diabetic retinopathy are needed to reduce visual disturbances due to diabetes mellitus. This research was a literature review using three databases, namely Google Sholar, PubMed, ProQuest, and Dimensions, and was published in 2017-2021. A total of 11 articles with a cross-sectional design met the criteria. The results show that the shortest duration of diabetes is one year, and the longest is >10 years, there are more male respondents than female respondents, and the age range is between 18-88 years. Knowledge related to diabetic retinopathy shows the poor result. Factors that influence knowledge are age, gender, religion, ethnicity, income, education level, occupation, marital status, diabetes duration, type of diabetes mellitus, patient perception, knowledge of systemic complications, and previous experience of visual impairment. Sources of information are from health staff, friends, or family of fellow sufferers and the media. Good knowledge is influenced by internal factors and external factors related to how to form a mindset and make decisions. The source of information obtained is used as a reference for knowledge and behavior formation. Providing education can be applied to increase patient knowledge about diabetic retinopathy.